Clinical Efficacy and Safety Comparison of Rivaroxaban and Dabigatran for Nonvalvular Atrial Fibrillation Patients Undergoing Percutaneous Left Atrial Appendage Closure Operation - Li, Xiaoye; Zhang, Xiaochun; Jin, Qinchun; Xue, Ying; Lu, Wenjing; Ge, Junbo; Zhou, Daxin; Lv, Qianzhou (Frontiers in Pharmacology, 2021)
Objective: Because of the clinical complexity of warfarin use, novel oral anticoagulation (NOAC) has been a feasible and safe alternative anticoagulant approach during left atrial appendage closure (LAAC). This study was designed to evaluate the efficacy and safety of rivaroxaban and dabigatran for non-valvular atrial fibrillation patients undergoing percutaneous LAAC. Methods: A single, prospective cohort study was conducted among patients who received anticoagulant with dabigatran or rivaroxaban. All patients were medicated with 3-month course of anticoagulation with NOACto facilitate device endothelialization, and followed by dual antiplatelet therapy until six months and then lifelong aspirin after discharge. Repeated transesophageal echocardiographic were scheduled to evaluate thrombosis formation on occluders and thrombus dissolution ability. Results: A total of 262 consecutive patients were initially enrolled, and finally 250 patients were analyzed in the end with 2 for procedure failure and 10 for loss of follow-up, of which 97 were from the dabigatran group and 153 were from the rivaroxaban group. There were 3(1.9%) in rivaroxaban and 8(8.2%) in dabigatran group experiencing device related thrombosis (DRT) events during follow-ups. Cumulative Kaplan-Meier estimates showed DRT was decreased under rivaroxaban treatment during the 6-month follow-ups (P=0.038*, OR=3.843, 95%CI:0.991 - 14.836). The shown TEE with average length and width of DRT in rivaroxaban group were significant decreased compared with dabigatran group (2.16 vs. 1.60 mm, P = 0.017* and 1.71 vs. 1.30 mm, P = 0.003*, respectively). The thrombosis dissolved after the switch from dabigatran or rivaroxaban to warfarin within the therapeutic range (INR 2.0-3.0) represented by average length and widthof thrombus with cooperation of secondary TEE for dabigatran and rivaroxaban group (0.64 vs. 0.40 mm, P = 0.206 and 0.43 vs. 0.27 mm, P = 0.082, respectively). There was no significant difference between the two groups with respect to the levels of coagulation parameters, cardiac function and bleeding occurrence. Conclusions: As compared to dabigatran, post-procedural rivaroxaban administration was a more feasible and safe alternative to prevent DRT complications expected after LAAC without increasing the risk of bleeding.